The First Photometric Study Of The Binary System Css J003106.8+313347 - Paki, E.; Poro, A.; Baudart, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We performed the first photometric study of the CSS J003106.8+313347 W Ursae Majoris (WUMa)-type system based on ground-based observations. We extracted times of minima from our observations and proposed a linear ephemeris based on the increasing incline of the orbital period using a Markov chain Monte Carlo (MCMC) approach. The PHOEBE Python code and the MCMC approach were used for the light curve analysis. This system did not need starspots for the light curve analysis. Mass ratio, fillout factor, and inclination were obtained as 0.699, 0.322, and 60o.6 respectively. We also estimated the absolute parameters of the system using the Gaia DR3 parallax. Therefore, the masses, radii, and luminosities have been determined to be M1 = 1.675, M2 = 1.171, R1 = 1.292, R2 = 1.097, L1 = 1.348, and L2 = 1.221. The orbital angular momentum J0 of the CSS J003106.8+313347 illustrates that this system is located in a region of contact binaries. The positions of the primary and secondary components on the Hertzsprung-Russell (HR) diagram are depicted. Проведено первое фотометрическое исследование системы CSS J003106.8+ 313347 типа W Ursae Majoris (W UMa) на основе наземных наблюдений. Из наших наблюдений извлечены времена минимумов и, используя метод Марковской цепи Монте-Карло (MCMC), предложена линейная эфемерида на основе увеличения наклона орбитального периода. Для анализа кривых блеска использовался код PHOEBE Python и метод MCMC. Для анализа данной системы не потребовалось учитывать звездные пятна. Получены отношение масс, фактор заполнения и наклон, равные 0.699, 0.322 и 60o.6 соответственно. Оценены также абсолютные параметры системы с использованием метода параллаксов Gaia DR3. Таким образом, массы, радиусы и светимости составили M1 = 1.675, M2 = 1.171, R1 = 1.292, R2 = 1.097, L1 = 1.348 и L2 = 1.221. Орбитальный момент импульса (J0) CSS J003106.8+313347 показывает, что эта система находится в области контактных двойных звезд. Положения первичных и вторичных компонентов изображены на диаграмме Герцшпрунга- Рассела (HR).
Keywords: Astrophysics